Efficient 3D trilateration algorithm for visible light positioning. (17th April 2019) - Plets, David; Almadani, Yousef; Bastiaens, Sander; Ijaz, Muhammad; Martens, Luc; Joseph, Wout
Abstract: This letter presents an efficient algorithm for estimating the three-dimensional (3D) location of a photodiode (PD) receiver via visible light positioning. It solely works on measured powers from different light-emitting diode (LED) sources and does not require any prior knowledge of the PD receiver height. It is found that four LEDs are required that are not on the same circle, in order to unambiguously determine the 3D location. The algorithm is optimized towards a minimized calculation time in view of real-time operation on energy-constrained lightweight and mobile devices such as drones.